Importance of Self-Care in Elderly Adults with Diabetes Mellitus - Ydalsys Naranjo Hernández; José Alejandro Concepción Pacheco (Revista Finlay, 2016)
Diabetes mellitus is a syndrome characterized by hyperglycemia which is caused by an absolute or relative deterioration of insulin secretion. It is a complex process of metabolism of carbohydrates, fats and proteins. It is a disease of prime importance at the level of public health worldwide, especially in the elderly people, as one of the most common non-communicable diseases, and the severity and diversity of its chronic complications. A very important element in relation to the treatment of diabetes mellitus is self-care. This perspective helps these patients to become aware of their own condition, by improving their knowledge and skills oriented toward positive behavior change, allowing them ultimately, reduce the risk of complications.